Teacher Management in Early Childhood Education - Dita Dewi (Early Childhood Research Journal (ECRJ), 2020)
This study aims to describe the planning, recruitment, coaching, and development at Surya Ceria Aisyiyah kindergarten, Cangakan, Karanganyar. This research is a qualitative descriptive study. Data collection uses observation techniques, interviews, and documentation. Test the validity of the data using technical triangulation and source triangulation. Data analysis using the model of Miles and Huberman namely the reduction stage, the stage of data presentation, and drawing conclusions.       The results of his research are (1) Planning in Surya Ceria Aisyiyah PAUD using job analysis and job analysis. (2) Recruitment of teachers in kindergarten Surya Ceria Aisyiyah, namely forming a committee for the recruitment of prospective new educators, announcements, administrative selection. The selection process for applicants in kindergarten Surya Ceria Aisyiyah includes administrative selection, written test, interview test, microteaching test. after the test ends, the overall test results will be discussed and determined which ones are accepted and rejected. Applicants who pass the selection face the school principal to be given directions related to the work contract and salary; (3) Guidance and development of educators through the identification of educator needs with evaluation methods. Forms of coaching and development in kindergarten Surya Ceria Aisyiyah Cangakan Karanganyar, namely supervision of school principals, seminars, workshops, training, In House Training, organization, training, visits, and comparative studies, further education.